1993
DOI: 10.1126/science.8430315
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Regulatory Complex of Escherichia coli III Glc with Glycerol Kinase

Abstract: The phosphocarrier protein IIIGlc is an integral component of the bacterial phosphotransferase (PTS) system. Unphosphorylated IIIGlc inhibits non-PTS carbohydrate transport systems by binding to diverse target proteins. The crystal structure at 2.6 A resolution of one of the targets, glycerol kinase (GK), in complex with unphosphorylated IIIGlc, glycerol, and adenosine diphosphate was determined. GK contains a region that is topologically identical to the adenosine triphosphate binding domains of hexokinase, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
264
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(278 citation statements)
references
References 52 publications
11
264
0
3
Order By: Relevance
“…Sargent et al 10 have described a C256R substitution in a patient with 12% GK activity. This amino-acid residue is located in a b-sheet close to domains involved in ATP binding, 22 and this may result in an enzyme with some residual activity. The insertion of an Alu sequence in intron 4 of the GK gene described by Zhang et al 11 does not effect the mRNA as judged from their RT-PCR analysis, but the residual GK activity was 32% of the mean normal control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sargent et al 10 have described a C256R substitution in a patient with 12% GK activity. This amino-acid residue is located in a b-sheet close to domains involved in ATP binding, 22 and this may result in an enzyme with some residual activity. The insertion of an Alu sequence in intron 4 of the GK gene described by Zhang et al 11 does not effect the mRNA as judged from their RT-PCR analysis, but the residual GK activity was 32% of the mean normal control.…”
Section: Discussionmentioning
confidence: 99%
“…Although the leucine 61 is only conserved in eukaryotes such as rat, mouse and Saccharomyces cerevisiae (Figure 5b), it is located in an a-helix on the outside of the GK subunit that interacts with another subunit to form the functional tetramer. 22 As proline residues are prone to interrupt helix formation, the mutation may cause a conformational change that influences the functioning of the GK protein.…”
Section: Discussionmentioning
confidence: 99%
“…The unphosphorylated form of IIA Glc inhibits transport of non-PTS sugars such as lactose, maltose, melibiose, and raffinose by interacting with transporters for these sugars (a process termed inducer exclusion) (1,(2)(3)(4). Other allosteric regulatory functions of IIA Glc include inhibition of the phosphorylation of glycerol by binding to glycerol kinase (5) and either inhibition or activation of adenylyl cyclase (6).…”
mentioning
confidence: 99%
“…In addition to sugar transport, multiple roles are exerted by the PTS and these include chemoreception (3), catabolite repression (4), carbohydrate transport and metabolism (1,5,6), carbon storage (7,8), and the coordination of carbon and nitrogen metabolism (9). More recently, we found that EIIA Glc of the PTS also regulates the flux between respiration and fermentation pathways by sensing the available sugar species via a phosphorylation state-dependent interaction with the fermentation/respiration switch protein FrsA (10).…”
mentioning
confidence: 99%